1971
DOI: 10.1037/h0030670
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of starvation-induced behavioral arousal in the rat.

Abstract: Spontaneous locomotor activity of neonatal and weanling rats was measured in stabilimeter activity cages scaled to the size of the animals under a wide range of temperature and food-deprivation conditions. Activity was low for the first 10 days of life and then increased sharply, reaching a peak nearly 10 times that of normal adult animals 16-20 days postpartum. Activity then declined rapidly to near-adult levels by 28 days of age. This dramatic change in the activity levels of the developing rat is correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
41
2

Year Published

1973
1973
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(50 citation statements)
references
References 26 publications
7
41
2
Order By: Relevance
“…Infant rats are vigilantly kept in the protective maternal nest by their mothers until around P17-P18 (Barnett, 1958;Galef & Clark, 1972; Pereira & Morrell, 2007;Small, 1899), when they are allowed out into their larger environment. At this point, they have full motor and sensory capacity (Moorcroft, Lyttle, & Campbell, 1971). Experiences at this point readily produce longCorrespondence concerning this article should be addressed to Kiersten S. Smith, Center for Molecular and Behavioral Neuroscience, Rutgers University, 197 University Avenue, Newark, NJ 07102.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infant rats are vigilantly kept in the protective maternal nest by their mothers until around P17-P18 (Barnett, 1958;Galef & Clark, 1972; Pereira & Morrell, 2007;Small, 1899), when they are allowed out into their larger environment. At this point, they have full motor and sensory capacity (Moorcroft, Lyttle, & Campbell, 1971). Experiences at this point readily produce longCorrespondence concerning this article should be addressed to Kiersten S. Smith, Center for Molecular and Behavioral Neuroscience, Rutgers University, 197 University Avenue, Newark, NJ 07102.…”
Section: Introductionmentioning
confidence: 99%
“…There is substantial information for adult rats, including diurnal locomotor activity and open-field activity measures (Joutsiniemi, Leinonen, & Laakso, 1991;Richter, 1922;Shirley, 1928), wheel running patterns (Bauer, 1990;Eikelboom & Mills, 1988;Peng, Jiang, & Hsu, 1980;Stewart, Rosenwasser, & Adler, 1985), rearing (Gregory, 1967;Hughes, Blampied, & Stewart, 1975;Kalinichev, Easterling, & Holtzman, 2002), and grooming (Borchelt, 1980;Jolles, Rompa-Barendregt, & Gispen, 1979;Sachs, 1988). Studies examining young rats focus mostly on adolescents (Barron, Hansen-Trench, & Kaiser, 1996;Campbell & Mabry, 1973;Hastings, Cooper, Bornschein, & Michaelson, 1977;Kalsbeek, de Bruin, Matthijssen, & Uylings, 1989;Livesey & Egger, 1970), although a few studies have been done in the infant rat.Simple measures of total activity demonstrate that infants are generally more active in the dark than in the light phase of the daily cycle (Bolles & Woods, 1964;Norton, Culver, & Mullenix, 1975), have considerable locomotor capacity (Moorcroft et al, 1971;Norton et al, 1975), are capable of rearing and grooming (Campbell & Mabry, 1973), and are capable of wheel running (Dalton-Jez & Eikelboom, 2005). Environmental novelty or familiarity significantly influences adult activity (Buelke-Sam, Sullivan, Kimmel, & Nelson, 1984;Galani, Duconseille, Bildstein, & Cassel, 2001), and some infant studies have a limited consideration of this (Buelke-Sam et al, 1984;Eilam & Golani, 1988;Golani et al, 2005;Pappas, Vickers, Buxton, & Pusztay, 1982).…”
mentioning
confidence: 99%
“…The rapid acquisition of DRL behavior by young rats of both sexes in light of the much poorer performance by adult males in earlier studies was surprising considering what is known of the ontogeny of activity (e.g., Moorcroft, Lytle, & Campbell, 1971) and passive avoidance behavior (Riccio, Rohrbaugh, & Hodges, 1968;Schulenburg, Riccio, & Stikes, 1971) in the rat. We suspected that the apparently better performance by younger males might reflect some procedural difference between the earlier study with adults (Beatty, 1973) and Experiment I.…”
Section: Experiments IImentioning
confidence: 99%
“…In the previous passive avoidance research, the suppression measure depended on the nonresponse of the subject. Since previous research had shown that there was an age difference in activity (Moorcroft, Lytle, & Campbell, 1971), the obtained age difference in suppression in the passive avoidance studies may have been influenced by this factor.…”
mentioning
confidence: 96%